A two-step mode of stripe formation in the Drosophila blastoderm requires interactions among primary pair rule genes. - Hartmann, C.; Taubert, H.; Jackle, H.; Pankratz, M.J. (Mechanisms of Development, 1994)
The stripe pattern of pair rule gene expression along the anterior-posterior axis of the Drosophila blastoderm embryo represents the first sign of periodicity during the process of segmentation. Striped gene expression can be mediated by distinct cis-acting elements that give rise to individual stripe expression domains in direct response to maternal and first zygotic factors. Here we show that the expression of stripes can also be generated by a different, two-step mode which involves regulatory interactions among the primary pair rule genes hairy (h) and runt (run). Expression of h stripes 3 and 4 is directed by a common cis-acting element that results in an initial broad band of gene expression covering three stripe equivalents. Subsequently, this expression domain is split by repression in the forthcoming interstripe region, a process mediated by a separate cis-acting element that responds to run activity. This second mode of pair rule stripe formation may have evolutionary implications.